The Unveiling Ceremony - Mumbai Archive Project Team (Jio Institute, 2024)
The unveiling ceremony highlights the pivotal event of Good Friday: the crucifixion of Jesus Christ. It serves as a reminder of the suffering and sacrifice Jesus endured for the redemption of humanity’s sins. This ceremony encourages the faithful to reflect on their own lives in light of Christ’s sacrifice and to seek forgiveness for their sins.